Scenarios for potential macroeconomic impact of Brexit on Hungary - László Békési; Zsolt Kovalszky; Tímea Várnai (Magyar Nemzeti Bank, 2017)
The purpose of this paper is to illustrate the economic impact mechanism of the secession of Great Britain from the European Union (Brexit) on the Hungarian economy, and to quantify the domestic growth risks. Several international studies have dealt with this topic using partial analysis and model based simulations, but only partial analyses are available regarding the Hungarian economy. Our analysis provides a broader picture by using the new macroeconomic forecast model of the MNB. Upon determining the exogenous assumptions in our simulations we relied on the central bank experts' broad knowledge. The applied model handles the wealth heterogeneity in the decision making processes of the households and the corporate sector. This feature makes the model suitable for explaining prolonged after-crisis recovery and the role of the financial accelerator feedback mechanism. In the course of illustrating the economic impact mechanism we show the main channels through which Brexit can spread over to Hungarian economic growth. Besides the primary channels, our analysis includes the secondary channel effects increasingly in the spotlight: we investigate the shock resilience ability of the financial system, and analyze the potential room for manoeuvre for fiscal policy.
Keywords: E27; E66; 330; Macroeconomic modelling; Simulation; Alternative Scenarios; Brexit; Economic Outlook